2001
DOI: 10.1046/j.1469-0691.2001.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of Toxoplasma gondii DNA in human body fluids by TaqMan polymerase chain reaction

Abstract: The potential application of this method to detect Toxoplasma DNA in body fluids and to follow the development of parasitemia under therapy could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
2
38
0
4
Order By: Relevance
“…Indeed, in literature, the standard curve is usually constructed from a serial dilution of T. gondii DNA or plasmid containing a known number of the target sequence (Reischl et al, 2003;Romand et al, 2004). Only Kupferschmidt et al (2001) have reported a standard curve from a serial-dilution of tachyzoites in human body fluids. The real quantification proposed in this report seems particularly interesting to us if it is confirmed that the quantification of T. gondii is useful to establish a prognosis of congenital toxoplasmosis (Costa et al, 2001;Romand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in literature, the standard curve is usually constructed from a serial dilution of T. gondii DNA or plasmid containing a known number of the target sequence (Reischl et al, 2003;Romand et al, 2004). Only Kupferschmidt et al (2001) have reported a standard curve from a serial-dilution of tachyzoites in human body fluids. The real quantification proposed in this report seems particularly interesting to us if it is confirmed that the quantification of T. gondii is useful to establish a prognosis of congenital toxoplasmosis (Costa et al, 2001;Romand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PCR is the major breakthrough for the diagnosis of this infection due to T. gondii. Moreover, real-time PCR has recently emerged as an improvement in the reliability of PCR assays (Lin et al, 2000;Costa et al, 2001;Kupferschmidt et al, 2001;Reischl et al, 2003;Romand et al, 2004). Since real-time PCR does not require the tubes to be opened after amplification, the risk of contaminating environment Article available at http://www.parasite-journal.org or http://dx.doi.org/10.1051/parasite/2007142149…”
Section: Introductionmentioning
confidence: 99%
“…The detection of T. gondii DNA in blood has highlighted the possibility to anticipate the diagnosis compared with radiological findings and histology. 4,5 However, the reliability of the PCR tests is crucial to evaluate the prevalence of Toxoplasma reactivation when the detection of circulating DNA is the only clue to its reactivation.…”
mentioning
confidence: 99%
“…The PCR procedures were as follows: one nested PCR 6 and analysis of PCR products in ELISA microplates; one single run PCR 1 and analysis in ELISA microplates; one real-time quantitative PCR assays with hybridization probes (LightCycler technology, Roche Molecular Biochemicals, Meylan, France); 4 and one both a nested PCR 3,7 and a real-time PCR with a hydrolysis probe (TaqMan technology, Applied Biosystems, Courtaboeuf, France). 5 The target DNA was the T. gondii B1 gene for the four laboratories, plus the 18 S rDNA for center 3. However the primers used for the B1 gene were different.…”
mentioning
confidence: 99%
See 1 more Smart Citation